Distinct plasma chemokines and cytokines signatures in Leishmania guyanensis-infected patients with cutaneous leishmaniasis - Mesquita, Tirza Gabrielle Ramos de; Junior, José do Espírito Santo; Silva, Luan Diego Oliveira da; Silva, George Allan Villarouco; Araújo, Felipe Jules de; Pinheiro, Suzana Kanawati; Kerr, Herllon Karllos Athaydes; Silva, Lener Santos da; Souza, Luciane Macedo de; Almeida, Samir Assad de; Queiroz, Krys Layane Guimarães Duarte; Souza, Josué Lacerda de; et al. (Frontiers in Immunology, 2022)
The immunopathology associated with Leishmaniasis is a consequence of inflammation. Upon infection with Leishmania, the type of host-immune response is determinant for the clinical manifestations that can lead to either self-healing or chronic disease. Multiple pathways may determine disease severity. A comparison of systemic immune profiles in patients with cutaneous leishmaniasis caused by L. guyanensis and healthy individuals with the same socio-epidemiological characteristics coming from the same endemic areas as the patients is performed to identify particular immune profile and pathways associated with the progression of disease development. Twenty-seven plasma soluble circulating factors were evaluated between the groups by univariate and multivariate analysis. The following biomarkers pairs IL-17/IL-9 (ρ=0,829), IL-17/IL-12 (ρ=0,786), IL-6/IL-1ra (ρ=0,785), IL-6/IL-12 (ρ=0,780), IL-1β/G-CSF (ρ=0,758) and IL-17/MIP-1b (ρ=0,754) showed the highest correlation mean among the patient while only INF-γ/IL-4 (ρ=0.740), 17/MIP-1b (ρ=0,712) and IL-17/IL-9 (ρ=0,707) exhibited positive correlation among the control group. The cytokine IL-17 and IL1B presented the greater number of positive pair correlation among the patients. The linear combinations of biomarkers displayed IP-10, IL-2 and RANTES as the variables with the higher discriminatory activity in the patient group compared to PDGF, IL-1ra and eotaxin among the control subjects. IP-10, IL-2, IL-1b, RANTES and IL-17 seem to be predictive value of progression to the development of disease among the Lg-infected individuals.